Features of Dictamnus albus (Rutaceae) in the pregenerative period of ontogeny in M. M. Gryshko National Botanical Garden in Ukraine - GnatiukА. М. (Regulatory Mechanisms in Biosystems, 2019)
Investigation of plant ontogenetic peculiarities and establishment of boundaries of ontogenetic states of individuals is a necessary basis for studying their populations. The minimal amount of data on morphology of plants in the pregenerative period of ontogenesis complicates plant identification in natural and cultural populations. Such information is especially important for rare species of plants. Dictamnus albus L. is a perennial rare plant listed in the Red Book of Ukraine.The objective of this research is to analyze the peculiarities of ontomorphogenesis of D. albus, to establish diagnostic signs of age stages and the sequence of their passage for identification of the multivariance of development. The results of the study on D. albus ontomorphogeny in the latent and pregenerative period at the M. M. Gryshko National Botanical Garden оf the National Academy of Sciences of Ukraine are represented in this article. Diagnostic features of age stages: seeds, seedlings, juvenile, immature, virginile are established. The study shows a multivariate development that reveals different sequences of passing ontogenesis states by individuals and, accordingly, the rate of their aging and life expectancy. To describe the variation of the passage by individuals of ontogeny stages, we divided the stages into ontomorphs, which determined the degree of development-degradation of plants. The research showed that every age stage lasts for one growing season or longer. The first bloom in plants does not come earlier than the sixth year of vegetation. Seedlings and juvenile plants vary in leaf number and phyllotaxy. The development of immature plants takes place from the third year of vegetation. Seedlings, juvenile and young immature plants have a tap-root system. In individuals older than 4 years a root system forms which becomes similar to the fibrous root system due to the presence of several thickened roots. In immature and virginile plants, we observed the formation of adventitious roots on the caudex. It has been found that D. albus is characterized by heterophylly and morphological variability of leaves, which is developed during ontogeny and shoot formation. The variety of the architecture of individuals in the early stages of ontogenesis and the multi-variation of their development indicate the variation of the reaction rate.The data may be used for evaluate age (ontogenetic) structure of D. albus populations.